2006
DOI: 10.1371/journal.pmed.0030231
|View full text |Cite
|
Sign up to set email alerts
|

Sacred Cows and Sympathetic Squirrels: The Importance of Biological Diversity to Human Health

Abstract: Dobson and colleagues describe how some host species act to reduce the risk of transmission of virulent zoonotic pathogens to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 19 publications
1
109
1
2
Order By: Relevance
“…For example, Harris and colleagues (Harris et al, 2009) found that interactions between pathogenic and non-pathogenic microbes on amphibian skin communities could help regulate disease. Second, the loss of species from temperate areas where local diversity is lower could cause proportionately greater increases in disease risk because of the smaller number of dilution hosts in the system (Fig.6) (Ostfeld and Keesing, 2000b;Dobson et al, 2006). Modeling and empirical efforts suggest that the consequences of species loss will be greatest Relative importance of species loss Latitude Latitude Species richness Dilution effect Relative importance of ind.…”
Section: How Does the Relationship Between Diversity And Disease Varymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Harris and colleagues (Harris et al, 2009) found that interactions between pathogenic and non-pathogenic microbes on amphibian skin communities could help regulate disease. Second, the loss of species from temperate areas where local diversity is lower could cause proportionately greater increases in disease risk because of the smaller number of dilution hosts in the system (Fig.6) (Ostfeld and Keesing, 2000b;Dobson et al, 2006). Modeling and empirical efforts suggest that the consequences of species loss will be greatest Relative importance of species loss Latitude Latitude Species richness Dilution effect Relative importance of ind.…”
Section: How Does the Relationship Between Diversity And Disease Varymentioning
confidence: 99%
“…The use of non-human decoys (e.g. livestock) to divert feeding mosquitoes away from humans may reduce vector-borne infections in the short term, but the increase in successful blood meals has the potential to cause long-term increases in mosquito populations and thereby increase the risk of subsequent human exposure (Saul, 2003;Dobson et al, 2006).…”
Section: Apparent Facilitation and The Net Effects Of Diversitymentioning
confidence: 99%
“…For instance, theoretical research has shown that predation and competition can influence rates of parasite infection by altering the population densities of hosts and vectors with varying degrees of competency (McCallum et al 2001, Packer et al 2003, Ostfeld and Holt 2004, Dobson et al 2006). Higher host densities can either increase density-dependent transmission (Ostfeld and Holt 2004) or reduce per capita exposure, when the source of infection is at least temporarily independent of host density (Raffel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This concurrence raises the possibility of a causal link between the two events and, with even larger future biodiversity declines expected, raises concerns for the future. Various investigators hypothesize that at the boundaries between areas of human habitation and human vacancy, animal biodiversity may prevent nonhuman pathogens from making the evolutionary transition to humans [29,30]. Nonetheless, animals in these areas still act as pathogen reservoirs that may contain organisms with the traits necessary to infect humans, a problem that becomes more acute as biodiversity and animal population sizes dwindle and pathogens or their vectors become more likely to encounter humans [31].…”
Section: Humans Biodiversity and Pathogens: The Future Of Infectioumentioning
confidence: 99%